Sedimentological Influence on Physical Properties of a Tight Sandstone Reservoir: The Cretaceous Nenjiang Formation, Southern Songliao Basin, Northeast China - Wang, Jinkai; Fu, Jialin; Wang, Jieming; Zhao, Kai; Zhang, Jinliang; Liu, Jifu (Frontiers in Earth Science, 2021)
At the beginning, Nenjiang Formation in the south of Songliao basin was not considered as a favorable reservoir for hydrocarbon accumulation, which led to its low described and characterized degree. In recent years, many oil and gas bearing units have been found in this area, but the cognitive level of the reservoir is not enough to support a reasonable and efficient development strategy. Therefore, it is necessary to conduct detailed study on the sedimentary microfacies and reservoir characteristics. This paper aims to solve these problems effectively and provide a reliable conclusion of fine reservoir characterization. First, nine single lithofacies types and 5 combined lithofacies types were identified according to core sequence, and their characteristics were described in detail. Then, the sedimentary model of river delta front in the study area was established, which could be divided into four sedimentary microfacies: underwater distributary channel, mouth bar, sand sheet, and distributary. The distribution law of sandbodies was made clear, that is to say, they extend to the south in a tongue like form, and their thickness gradually decreases until they are pinched out. Finally, the influence degree of sedimentation on reservoir properties was analyzed by establishing the correlation between microfacies and reservoir physical parameters, such as porosity, permeability, pore radius, throat radius and clay minerals. It is revealed that the correspondence between reservoir physical properties and microfacies types is very good, and the control of microfacies types on reservoir physical properties is clear.